(untitled) (Research, Society and Development, 2020)
This article aimed to analyze the approach to the health theme in the Base Nacional Comum Curricular and their teaching prospects in Early Childhood Education and the early years of Elementary School. For this, a study of the type of documentary research was developed. Initially, the preliminary documentary analysis of the Base Nacional Comum Curricular, in the stages of Early Childhood Education and early years of Elementary School, seeking the health theme. From this preliminary analysis, the following research question was elaborated: What are the possibilities of approaching the theme of health and health promotion in these teaching stages? Then, the document was thoroughly read in the teaching stages of interest, seeking to answer the question. As a result, it is worth pointing out that health-related topics in the school context do not appear only through the word health, but implicit in several skills and competences to be developed. Thus, it is possible to explore the theme from the development of other skills, such as, act with autonomy and responsibility, exercise empathy and cooperation, value and use historically constructed knowledge, considering so, the specificities of the place where the child is inserted so that interaction with scientific knowledge occurs and, consequently, more meaningful learning.